Set Partitions and the Multiplication Principle. Issue 2 (7th February 2016) - Lockwood, Elise; Caughman, John S.
Abstract: To further understand student thinking in the context of combinatorial enumeration, we examine student work on a problem involving set partitions. In this context, we note some key features of the multiplication principle that were often not attended to by students. We also share a productive way of thinking that emerged for several students who were then able to resolve the issues in question. We conclude with pedagogical implications.